The Implementation of the Inquiry Method Using Audiovisual Media to Improve Students' Engagement and Learning Outcomes in Civics Education - Yeremias Miwa; Nani Mediatati; Dionisius Heckie Puspoko Jati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Technological advancements and evolving learning methods demand innovation in education, particularly to enhancing student engagement and learning outcomes in the subjects of Pancasila and Civic Education. This study aims to improve student activity and learning outcomes by implementing the inquiry method assisted by audiovisual media. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. The research subjects were 36 students from Class XI Welding Engineering at State Vocational High School 3 Salatiga. Data collection techniques included observation, interviews, and tests. The results showed that in the pre-cycle stage, only 16.66% of students were actively involved in the learning process, and 41.7% achieved a score of ≥ 75. In Cycle I, student engagement increased to 75.6%, and learning mastery rose to 58.3%. In Cycle II, student activity reached 90.9%, with learning mastery improving significantly to 91.6%. The findings conclude that the inquiry method supported by audio-visual media is effective in enhancing student engagement, understanding, and academic performance. Keywords: inquiry method, learning activities, learning outcomes, civic education